Enantioselective epoxidation by the chiral auxiliary approach: Asymmetric total synthesis of (+)‐Ambrisentan. (21st February 2021) - Madhu, Madasu; Doda, Sai Reddy; Begari, Prem Kumar; Dasari, Krishna Rao; Thalari, Gangadhar; Kadari, Sudhakar; Yadav, Jhillu Singh
Abstract: Enantioselective and a highly concise total synthesis of Ambrisentan are described. The chiral auxiliary controlled enantioselective epoxidation (Azerad protocol), photochemical regioselective epoxide opening, and base mediated ester hydrolysis reactions are the key reactions. Abstract :